Dynamic vulnerability assessment of maize under low temperature and drought concurrent stress in Songliao Plain - Yunmeng Zhao; Mula Na; Ying Guo; Xingping Liu; Zhijun Tong; Jiquan Zhang; Chunli Zhao (Agricultural Water Management, 2023)
With global climate change, most parts of the world face more than one natural disaster. Field crops must cope with a combination of two or more stresses. System vulnerability has changed, and quantitative vulnerability analysis is imminent and challenging. Based on the crop water surplus deficit index (CWSDI) and low-temperature index (LTC), this study used the copula method to establish a dynamic assessment model of maize vulnerability under different low temperature and drought concurrent stress intensities, finally showed it in two forms of three-dimensional surface and spatial distribution, which was more vivid and comprehensive. The main conclusions are as follows: the peak number of individual events and concurrent events of low temperature and drought is significantly different, the time trend of the number of concurrent events in each growth period is not the same, and the interannual difference is significant; low-temperature severity and maize yield loss rate, low-temperature severity, and drought severity had significant correlation. Based on this, a 3 C-vine-copula model was established and passed the test. The interaction between the joint probability of concurrent event intensity and the loss rate leads to complex changes in vulnerability. When low temperature and drought are concurrent, the vulnerability analysis cannot be simply superimposed by low temperature and drought intensity. The vulnerability distribution of maize at different growth stages in Songliao Plain shows noticeable regional differences. The central and southern parts of the study area are the most vulnerable areas under low-temperature and drought stress. This study’s results can help managers adjust agricultural resources and adopt more effective irrigation policies under combined stress conditions.